(untitled) (Strathmore Law Review, 2020)
The teachers’ right to strike and the children’s right to education are both essential rights recognised by national and international laws in Kenya. Despite this fact, there are instances where conflicts arise between these two rights. The courts have a mandate to balance competing human rights in instances of conflict. However, whenever there has been a conflict between the two rights, Kenyan courts have issued injunctions that require public-school teachers to suspend their strike. By doing so, the courts are leaving the teachers with no effective alternative mechanism to address their pertinent needs. The question of how a balance between the teachers’ right to strike and the children’s right to education in Kenya can be attained is thus an essential concern that is at the focal point of this paper. In a bid to address this question, Kenya’s Constitution, Children’s Act, Labour Relations Act, and case law from the Court of Appeal; namely, TSC v KNUT & 3 others, are analysed to reveal Kenya’s position on the two rights and the various balancing approaches available.